Evaluating the performance of intermediate-level science teachers in Taif in light of some teaching competencies from their perspective - Al-Harthi, Samar Safr (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to evaluate the performance of science teachers at the intermediate stage in the city of Taif in light of some teaching competencies from their point of view. The descriptive (survey) method was used. The study sample consisted of (114) science teachers who were selected by a stratified random method, representing (56.44%) of the study community. For the purpose of collecting data, the researcher prepared a questionnaire consisting of (31) indicators, distributed over two axes; Lesson implementation competencies, including (18) indicators, and lesson evaluation competencies, including (13) indicators. After verifying the validity and reliability of the tool, it was applied to the aforementioned sample. The study results showed that female teachers highly rated their possession of lesson implementation competencies, with an overall average of (4.34) out of (5), representing a percentage of (86.80%). The lesson evaluation competencies axis was also highly rated, with an overall average of (4.33), representing a percentage of (86.60%). The study results also revealed no statistically significant differences at the significance level (α≤0.05) in the responses of the study sample attributed to the variables (qualification, specialization, and years of experience). In light of the results, the study recommended enhancing cooperative learning competencies in classrooms among female teachers, adopting new evaluation methods such as performance evaluation, and focusing on enhancing the efficiency of analyzing and interpreting exam results among female teachers.